Coeficiente de cultura (Kc) para o milho pipoca-grupo everta (Zea mays L. cv. CMS-43/EMBRAPA) - Oliveira, Osvaldo José de (1995)
With the purpose ofestablishing the crop coefficient (Kc), of pop corn, Zea mays L, genetical group everta cv. CMS-43/EMBRAPA, an experiment in a array of three non-weighing lysimeters type Thornthwait - Mather, underirrigation-fed, cultivated to pop corn and on a array of three lysimeters under the same conditions, grown to grass (Paspaium notatun Flugge), was conducted at the Biology Department, sector of Bioclimatology at the Universidade Federal de Lavras-MG (21° 14'S; 45° OOWw and 918,84 m). Adaily water balance on all the lysimeters was acomplished over the period encompassed during the cycle of corn cultivation, obtaining the maximum evapotranspiration of the crop and reference evapotranspiration. For the period considered, 12 empirical methods of climatological correlation for evaluating the reference evapotranspiration were compared (Penman, Solar Radiation, Class ATank, Blaney &Criddle, Linacre, Thornthwaite, Hamon, Hargreaves, Makkink, Papadakis, Budyko and modified Penman), with the values determined through the lysimetrical tanks. The values for the reference evapotranspiration (ETo), of the evaluation methods; Penman, Linacre, modified Penman, Solar Radiation, Class A Tanks and Blaney &Criddle are those which best fitted, showing determination coefficient (R2), equal to 96,79%, 91,06%, 87,28%, 81,98%, 88,34% and 87,72% respectively. Leaf area index-LAI, as acharacterístic of the plant explained the water uptake curve by the corn plants well. The maximum evapotranspiration (ETmax.), on adaily average, of pop corn was equal to 2.62 mm . day⁻¹ and reference evapotranspiration (ETo), of grass equal to 3.5 mm.day⁻¹ .The variables ETmax. and ETo were correlated aiming at the obtaining of the crop coefficient (Kc). The crop had its cycle divided into four developmental steps according to that suggested by Doorenbos &Pruitt (1977), besides, the initial step.Each step was characterized, by the acumulation of day-degrees - method Brown, obtaining: initial step, 170,10 day-degrees and 15,30 mm of water, step I, 687,32 daydegrees and 52,60 mm of water; step II, 928,04 day-degrees and 46,80 mm of water, step III, 1.099,74 day-degrees and 195,35 of water and step IV, 618,13 day-degrees and 73.20 mm of water. The length of each step in calendar days were: 6, 35, 25, 50 and 30 days respectively, steps: initial, I, II, III and IV.The crop coefficient measured for steps I, II, III and IV were respectively 0.49, 0.56, 1.19 and 0,73 and it may be calculated by the equation: Kc =1,04 - 0.0017.GD +0,13⁻⁵.10_5.GD² - 0.26.10⁻⁹ GD³, showing determination coefficient (R2) equal 81,46% for the level 5% for probability.